Thực trạng đào tạo kiến thức thông tin tại một số thư viện đại học Việt Nam - Trương, Đại Lượng (2021)
Presents results of investigation into information literacy training at 6 university libraries in Vietnam; indicates clearly the objectives, scope, method and concrete results of this study; sets forth some recommendations on quality enhancement of information literacy training in universities